Implementasi E-Office Melalui Aplikasi Bagelen Pada Kecamatan Cibinong Kabupaten Bogor - Rusliandy Rusliandy; Apid Junaedi; Syahrul Ramadhan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2022)
The research focused on the implementation of the Bagelen application in Cibinong District with an analysis knife using the Edward III concept, namely from the aspects of communication, disposition, bureaucratic structure and resources. The method used is a qualitative approach with data collection techniques through interviews, observation and reference studies, as well as data analysis using source triangulation. The results of the study stated that the bagelen application had been running since 2021 and had a positive impact on government organizations and apparatus. However, in its implementation it is still faced with the following problems: (1) limited and passive quality of human resources. (2) the lurah's commitment is not optimal. (3) SOP has not been established in application management, and a decision letter has not been issued regarding the determination of the person in charge of implementing the application. (4) application development was built with sub-district self-help, and the existing infrastructure is still limited. In order to effectively implement the bagelen application policy in Cibinong sub-district, Bogor regency, the things that must be done are: (1) improve information technology competence for operators, and provide warning and motivation to be active in application management. (2) The sub-district head orders the lurah to commit to supporting the application. (3) The sub-district needs to immediately issue a decree on SOP and the official in charge of implementing Bagelen. (4) the need for support from the Bogor district government in terms of budget and infrastructure